RNA editing and mitochondrial genomic organization in the cryptobiid kinetoplastid protozoan Trypanoplasma borreli. - Maslov, D A (1994)
The bodonids and cryptobiids represent an early diverged sister group to the trypanosomatids among the kinetoplastid protozoa. The trypanosome type of uridine insertion-deletion RNA editing was found to occur in the cryptobiid fish parasite Trypanoplasma borreli. A pan-edited ribosomal protein, S12, and a novel 3'- and 5'-edited cytochrome b, in addition to an unedited cytochrome oxidase III gene and an apparently unedited 12S rRNA gene, were found in a 6-kb fragment of the 80- to 90-kb mitochondrial genome. The gene order differs from that in trypanosomatids, as does the organization of putative guide RNA genes; guide RNA-like molecules are transcribed from tandemly repeated 1-kb sequences organized in 200- and 170-kb molecules instead of minicircles. The presence of pan-editing in this lineage is consistent with an ancient evolutionary origin of this process.